Práticas pedagógicas na educação a distância: deslocamento de memórias e sentidos - Nogueira, Vanessa dos Santos (2012)
This work is a Master Thesis on Education, developed in the Graduate Program in Education, Federal University of Santa Maria (UFSM), it follows line of research School Practices and Public Policy. Its general objective: to analyze the meanings produced in the speech of teachers and tutors on the constitution of their pedagogical practices in distance education mode. The research was characterized as qualitative guided theoretic-methodological approach the Discourse Analysis (AD) of French School. The study was developed from the discourse of teachers and tutors of the Distance Education Course of the Federal Santa Maria University (UFSM), under the System at the Open University of Brazil (UAB), on their teaching practices and understanding about the movement established between them to actualize the teaching, placed in the context of public policy. In which, the advent of distance learning and Information Communication Technologies, mobilized from public policies, causing [re] building in the processes of teaching and learning in Higher Education. The meanings produced in the speech of teachers and tutors on the constitution of their pedagogical practices in the form of distance education are presented in an in-between place where the EAD, as well as researched and presented in this thesis, is undergoing a process of naturalization of both their possibilities as the conquest of recognition between the existing educational arrangements.